ОРОЗМОВЛЕННЯ ЯК СТИЛЕТВІРНА ОЗНАКА ХУДОЖНЬОЇ ПРОЗИ П.ХХІ СТ. / CONVERSATIONALIZATION AS STYLISTIC ATTRIBUTE OF THE XXTH CENTURY IMAGINATIVE LITERATURE - Марія ЦУРКАН (Aktualʹnì Pitannâ Suspìlʹnih Nauk ta Istorìï Medicini, 2016)
Цуркан М. В. Разговорность как стилевой признак художественной прозы н.ХХI века. В статье рассмотрено понятие "разговорность" в аспекте истории и стилистики украинского языка. Представлен анализ структурно-семантических, ареальных и функциональных параметров лексических и фразеологических средств стилизации разговорности, которые охватывают общепринятую и функционально ограниченную разговорную лексику, имена для выполнения номинативной, этнографической и экспрессивно-выразительных функций. Ключевые слова: речь прозы, разговорность, стилизация разговорности, бытовизм, диалектизм, этнографизм, росиянизм, жаргонизм, сленгизм, фразема, комуникема. Tsurkan M. V. Conversationalization as Stylistic Attribute of the XXth Century Imaginative Literature. The Article investegates an important linguo-stylistic problem of investigation of the stylistic potential of the colloquial elements in the language of Bukovinian writers of the beginning of the XXI century – M. Matyos, G. Tarasyuk, V. Kozhelyanko, M. Lazaruk, W. Michael. Functional-stylistic category of is considered as one of defining categories of the modern concepts of literary language development in general and of the language of belletristic literature in particular. Hence, models, approaches and techniques related to dynamics of literary-linguistic process are accumulated around conversationalization, its different vectors and modifications as means of stylization process dedicated to achievement of corresponding stylistic effects. This is especially true in the case of transmitting through the literary text the temporal and local coloring of the social types of a definite socio-cultural environment, specific features of the personages’ speech or in the cases when the author wants to stress upon the naturalness of the situations he describes. The stylistic category of conversalization includes a great number of artistic and figurative means of the national language. Among such linguistic means there could be mentioned lexical units with semantic and word-formative attributes of colloquial style, everyday domestic phraseology, colloquial syntax, phonographems actualizing the “sonic image of the word”, stylistic figures of play of words, models of anthroponomic formation and other means of conversalization stylization. In their correlation with individual linguistic practice of the Bukovinian writers the national and ethnomarked means of stylization (lexemes, phrasemes, comunikemes) altogether form the cultural-subject background and the linguistic characteristics of the personages in monologues, dialogues direct and indirect speech; typify the modern sociocultural conditions of daily life, mark the personages as representatives of certain subcultures at the same time underlining the image of personages. Key words: Language of prose, conversationalazation, stylization of conversationalization, domestic vocabulary, dialecthism, ethnographism, russianism, jargonism, slangism, frazem, komunikem.